Energy target achievement and its determinants in critically ill COVID-19 patients in Indonesia - Niken Puruhita; Febe Christianto; Luciana Sutanto; Banundari Rachmawati; Sofyan Harahap; Muchlis Ahsan Udji Sofro; Retnaningsih -; Riwanto; Hertanto Wahyu Subagio (World Nutrition Journal, 2021)
Introduction. Achievement of energy target in critically ill Covid-19 patients in Intensive Care Unit (ICU) is challenging. This study was aimed to depict the possibility of achieving energy target and its determinants in critically ill Covid-19 patients. Methods. A cross sectional study was conducted in ICU of dr. Kariadi Hospital Semarang, Indonesia. Secondary data were obtained from Covid-19 patients who were in ICU for minimum 3 days, from March to December 2020. Data collected included age, sex, Body Mass Index (BMI), comorbidities, Modified Nutrition Risk in Critically Ill (mNUTRIC) score, energy intake, route of nutrition delivery (enteral or combination of enteral and parenteral nutrition), lactate status, ICU length of stay (LOS), duration of mechanical ventilator and mortality. Risk Prevalence calculations were conducted to measure risks. Variables with significant associations and p< 0.25 were included in multiple logistic regression. Results. A total of 188 subjects were included in the analysis. Most patients were male (62.8%) and obese (61.8%). As much as 56.9% patients were able to achieve energy target of 20 kcal/kgBW on day 3 of ICU stay. Those with low risk mNUTRIC score and nutrition delivery was through enteral and parenteral route were more likely to achieve target energy of 20 kcal/kgBW in the first 3 days in the ICU. Conclusions. Achieving energy target of 20 kcal on day 3 of ICU stay for critically ill Covid-19 patients is feasible. Low mNutric score and nutrition delivery through enteral and parenteral route were two determinants for the achievement.